SÍNTESE E CARACTERIZAÇÃO DE ESPUMA DE VIDRO DOPADA COM PENTÓXIDO DE NIÓBIO - Andrade, Felipe Holtz de (2015)
The purpose of this work is the synthesis and characterizations of a glass foam using sodium hydroxide as the foaming agent, in addition to niobium pentoxide used as filler. For the synthesis of the foam, waste glass, sodium hydroxide and niobium pentoxide were mixed in a mold, dried and sintered at 800 oC. In follow, the foam was characterized by different methods: X-ray diffraction (XRD), thermogravimetric and diferential scanning calorimetry (DSC), Helium pycnometry, compression testing, high resolution electron microscopy field-emission gun (FEG) and chemical microanalysis energy dispersive x-ray spectroscopy (EDS). The result obtained was a glass foam with 36,50 % of porosity and 44,50 % increase in the compressive strenght by niobium pentoxide.